ANALISIS PERAN APARAT PENGAWAS INTERNAL PEMERINTAH (APIP) DALAM PENCEGAHAN DAN PENDETEKSIAN FRAUD BIAYA PERJALANAN DINAS (STUDI KASUS PADA INSPEKTORAT DAERAH PROVINSI SULAWESI UTARA) - Lumempouw, Eliska Gricy; Nangoi, Grace B.; Kalangi, Lintje (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
The risk of fraud in a government can be minimized by having an adequate internal control system. This system must be run by internal auditors who are expected to prevent and detect the fraud. Official travel expenses are activities that are always carried out by all Local Government Agency and its misuse can causing state and regional financial losses. Therefore, the fraud of official travel expenses has become a matter that highly highlighted by the public. Government Internal Supervisory Apparatus (APIP) as an internal government supervisor are expected to be able to carry out their functions to prevent and detect fraud, especially in official travel expenses. This research aims to analyze the roles of Government Internal Supervisory Apparatus (APIP) in preventing and detecting official travel expenses fraud at Regional Inspectorate of North Sulawesi. Moreover, this research also aims to identify the problems that Inspectorate faced in preventing and detecting fraud of official travel expenses. This research conducted using qualitative method, with case study approach. The data analysis in this research using the model of data analysis by Miles and Huberman (1984) that are data reduction, data display, and conclusion drawing/verification. The research result reveal that the Regional Inspectorate of North Sulawesi has been effectively doing the role of Government Internal Supervisory Apparatus (APIP) as assurance and consulting in preventing and detecting official travel expenses fraud. However, according to report of audit findings of Indonesian Audit Board (BPK) regional North Sulawesi in 2018 and 2019, there are findings related to the misuse of official travel expenses fraud. The problem that Inspectorate faced in preventing and detecting fraud of official travel expenses, that are: 1) the limited of time, human resource. and budget; 2) Lack of auditee participation in audits; 3) Lack of understanding of Risk-based audit; and 4) The consulting unit has not yet been established.